2018
DOI: 10.3389/fphys.2018.01398
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Aggravates Diet-Induced Coronary Artery Disease and Myocardial Infarction in SR-B1-Knockout/ApoE-Hypomorphic Mice

Abstract: Diabetes is a risk factor for development of atherosclerotic cardiovascular disease. Animal model studies in mice revealed that hyperglycemia increases development of atherosclerosis in the aorta as well as myocardial fibrosis in surgical models of coronary artery ligation; however, the impact of hyperglycemia on coronary artery atherosclerosis and subsequent heart disease is less clear. To investigate the effect of hyperglycemia on atherosclerosis and coronary heart disease, we used a mouse model of diet-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…these mice seems to be associated with myocardial infarction and resulting cardiac conduction and functional abnormalities (Nakatsu et al, 2017;Wang Q. et al, 2017;Gonzalez et al, 2018). However, these associations still need to be further investigated.…”
Section: Discussionmentioning
confidence: 97%
“…these mice seems to be associated with myocardial infarction and resulting cardiac conduction and functional abnormalities (Nakatsu et al, 2017;Wang Q. et al, 2017;Gonzalez et al, 2018). However, these associations still need to be further investigated.…”
Section: Discussionmentioning
confidence: 97%
“…This model is of specific interest due to the lack of small animal models resembling severe atherosclerosis symptoms (formation of advanced plaques), severe coronary heart disease, and even premature death seen in humans (59,60).…”
Section: Sr-bi Knock-out and Apoe-hypomorphic Micementioning
confidence: 99%
“…Whereas, type II diabetics are more likely to have obesity, peripheral arterial disease, history of transient ischemic attack, and stroke attributable to large-artery atherosclerosis [89]. In a recent study, Gonzalez et al [60] used streptozocin to induce hyperglycemia in SR-B1-knockout/hypoE mice. They reported that the SR-B1-knockout/hypoE hyperglycemic mice had an increased incidence of coronary artery atherothrombosis, myocardial infarction, and early death when on a high-fat, high-cholesterol diet [60].…”
Section: Sr-b1 and Diabetes Mellitusmentioning
confidence: 99%
“…In a recent study, Gonzalez et al [60] used streptozocin to induce hyperglycemia in SR-B1-knockout/hypoE mice. They reported that the SR-B1-knockout/hypoE hyperglycemic mice had an increased incidence of coronary artery atherothrombosis, myocardial infarction, and early death when on a high-fat, high-cholesterol diet [60]. SR-B1 was increased in type 2 diabetes patients, but not in those with hypercholesterolemia [90].…”
Section: Sr-b1 and Diabetes Mellitusmentioning
confidence: 99%